Resveratrol: The Multifaceted Roles and Mechanisms of Polyphenol to Improve Longevity, Immunomodulation, and Age-related Diseases - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2025)
High in polyphenols diet has been known to protect human against chronic metabolic diseases including cancer, diabetes, neurological and cardiovascular disorders. Resveratrol (RSV) is a natural polyphenol that presents in fruits, vegetables, and nuts. The polyphenols content of RSV possesses anti-inflammatory, antioxidant, immunomodulatory, and anticancer properties by influencing the nuclear factor-kappaB (NF-κB), p53, adenosine monophosphate-activated protein kinase (AMPK), mammalian target of rapamycin (mTOR), Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) pathways, enzymatic antioxidants expressions, and the levels of microRNAs. Therefore, this review article will focus on the potential of RSV in improving aging and metabolic diseases, which mostly induced by low-chronic inflammation and oxidative stress. RSV is also known as calorie restriction (CR)-mimetics to activate sirtuins family which improve mitochondrial function, repair DNA and genomic stability and reduce inflammation thus become a promising substance to extend health span and longevity. RSV can be useful as a supplement to prevent aging-related diseases, with a dose range between 250–1,000 mg depending on the intended health benefit and individual factors. More clinical data is needed to determine the impact of RSV metabolites and the relationship between dose, concentration, and effect, particularly in the context of chronic illness.KEYWORDS: mesenchymal stem cell, extracellular vesicle, exosome, cancer therapy, drug delivery